Present as a partner and a parent: Mothers' and fathers' perspectives on father participation in prenatal care. Issue 3 (5th May 2021) - Walsh, Tova B.; Carpenter, Emma; Costanzo, Molly A.; Howard, Lanikque; Reynders, Rachel
ABSTRACT: Supportive father involvement during pregnancy can positively impact maternal and child outcomes. Father participation in prenatal care is increasing, yet little research exists to understand how mothers and fathers experience father participation in prenatal care and their preferences for father participation. We interviewed expectant first‐time mothers ( N = 22) and fathers ( N = 20) to learn about fathers' participation in prenatal care, perceptions of providers' treatment of fathers, and preferences for father participation. Interviews were coded using principles of grounded theory. Father participation ranged from attendance at visits considered "important" (e.g., ultrasounds) to attendance at every appointment. Experiences of father participation varied, with many describing it as both an important act of support for the mother and part of assuming the role of father. Most participants saw great value in father participation in prenatal care as an opportunity for fathers to learn how to support a healthy pregnancy, bond with their developing baby, and share joy and/or worries with mothers. Participants generally felt that fathers were made to feel welcome and wanted providers to be inclusive of fathers during appointments. Results of this study suggest that father participation presents an opportunity for prenatal care providers to foster fathers' positive involvement in pregnancy, support for mothers, and preparation to parent. RESUMEN: El apoyo participativo del papá durante el embarazo puede tener un impacto positivo en el resultado materno y del niño. La participación del papá en el cuidado prenatal está aumentando, sin embargo, existe poca investigación para comprender cómo las mamás y los papás experimentan la participación del papá en el cuidado prenatal, y sus preferencias en cuanto a la participación del papá. Entrevistamos a madres primerizas embarazadas (N = 22) y papás (N = 20) para conocer acerca de la participación de los papás en el cuidado prenatal, las percepciones que acerca de los papás tenían quienes ofrecen el tratamiento, así como las preferencias en cuanto a la participación del papá. Se codificaron las entrevistas usando principios de teoría fundamentada. La participación del papá osciló desde el asistir a visitas consideradas "importantes" (v.g. el ultrasonido) hasta el asistir a cada cita. Las experiencias de la participación del papá variaron, y muchos las describieron como un acto importante de apoyo para la mamá y parte de asumir el papel de papá. La mayoría de los participantes vio un gran valor en la participación del papá en el cuidado prenatal, así como una oportunidad para los papás de aprender cómo prestar apoyo a un embarazo sano, establecer una relación con su bebé en desarrollo y compartir las alegrías y/o las preocupaciones con las mamás. Los participantes generalmente sintieron que a los papás se les hizo sentir bienvenidos y querían que quienes prestaban el cuidado incluyeran a los papás durante la cita. Los resultados de este estudio sugieren que la participación del papá presenta una oportunidad para quienes prestan el cuidado prenatal de fomentar una participación positiva en el embarazo, el apoyo a las mamás y la preparación para ser padre. RÉSUMÉ: La participation d'appui du père durant la grossesse peut affecter de manière positive les résultats maternels et l'enfant. La participation du père au soin prénatal augmente et cependant il existe peu de recherches permettant de comprendre comment les mères et les pères font l'expérience de la participation du père au soin prénatal et leurs préférences pour la participation du père. Nous avons interviewé des mères attendant leur premier enfant (N = 22) et des pères (N = 20) afin de découvrir la participation des pères au soin prénatal, les perceptions de manière dont les prestataires traitent les pères, et les préférences pour ce qui concerne la participation des pères. Les entretiens ont été codés en utilisant les principes de théorie ancrée. La participation du père est allée de la présence aux visites considérées comme étant "importantes" (comme par exemple les ultrasons) à la présence à chaque rendez‐vous. Les expériences de la participation des pères ont varié, la plupart des participants la décrivant comme étant à la fois un acte de soutien important pour la mère et une partie du fait d'assumer le rôle de père. La plupart des participants ont ressenti une grande valeur en la participation du père dans le soin prénatal, en la considérant comme une chance pour les pères d'apprendre comment soutenir une grossesse saine, de se lier avec leur bébé se développant et de partager la joie et/ou les inquiétudes avec les mères. Les participants ont généralement ressenti que les pères étaient bien accueillis et souhaitaient que les prestataires incluent les pères durant les rendez‐vous. Les résultats de cette étude suggèrent que la participation du père présente une opportunité pour les prestataires de soin prénatal de cultiver une participation positive des pères à la grossesse, au soin des mères et à la préparation au parentage. ZUSAMMENFASSUNG: Als Partner und als Elternteil präsent zu sein: Perspektiven von Müttern und Vätern auf eine Beteiligung des Vaters an der Schwangerschaftsvorsorge Eine unterstützende Beteiligung des Vaters während der Schwangerschaft kann sich positiv auf Outcomes von Mutter und Kind auswirken. Die väterliche Beteiligung an der Schwangerschaftsvorsorge nimmt zu, es gibt jedoch nur wenig Forschung dazu, wie Mütter und Väter die väterliche Beteiligung an der Schwangerschaftsvorsorge erleben und was sie sich dabei wünschen. Wir haben werdende Mütter (N = 22) und Väter (N = 20) befragt, um mehr über die väterliche Beteiligung an der Schwangerschaftsvorsorge und damit zusammenhängende Präferenzen zu erfahren. Außerdem wurde untersucht, wie der Umgang mit den Vätern wahrgenommen wird. Die Interviews wurden nach den Prinzipien der „Grounded Theory" kodiert. Die väterliche Beteiligung reichte von nur der Begleitung zu Untersuchungen, die als „wichtig" angesehen wurden (z. B. Ultraschall), bis hin zur Begleitung zu jedem Termin. Die väterliche Beteiligung wurde unterschiedlich wahrgenommen. Viele beschrieben sie sowohl als wichtigen Akt der Unterstützung der Mutter als auch als Teil der Übernahme der Rolle des Vaters. Die meisten Studienteilnehmenden sahen in der väterlichen Beteiligung an der Schwangerschaftsvorsorge einen großen Wert. Sie bietet für Väter die Gelegenheit zu lernen, wie sie eine gesunde Schwangerschaft unterstützen, eine Bindung zu ihrem sich entwickelnden Baby aufbauen und Freude und / oder Sorgen mit den Müttern teilen können. Die Studienteilnehmenden waren im Allgemeinen der Meinung, dass Väter sich willkommen fühlten, und wollten, dass Väter bei Terminen einbezogen werden. Die Ergebnisse dieser Studie legen nahe, dass die väterliche Beteiligung an der Schwangerschaftsvorsorge eine positive Einbindung von Vätern in die Schwangerschaft, die Unterstützung der Mütter sowie die Vorbereitung auf das Elterndasein fördert. 抄録: パートナーそして親としての存在:父親の出産前ケアへの参加に関する母親と父親の視点 妊娠中の父親の協力的な関わりは、母と子の転帰にプラスの影響を与える可能性がある。父親の出産前ケアへの参加は増えているが、母親と父親が父親の出産前ケアへの参加をどのように経験しているか、そして父親の参加に対する彼らの志向はどのようかを理解するための研究はほとんどない。初産婦の母親 (N = 22) と父親 (N = 20) に面接を行い、父親の出産前ケアへの参加、出産前ケアの提供者の父親の扱いの認識、父親の参加に対する志向について研究した。インタビューはグラウンデッド･セオリーの原則を用いてコード化された。父親の参加は、「重要」と見なされる受診 (超音波など) への同席参加から、すべての予約への参加まで多岐にわたった。父親の参加の経験はさまざまであり、母親をサポートする重要な行為であるとも、担うべき父親の役割の一部であるとも多くの人が述べた。ほとんどの参加者は、父親が健康な妊娠をサポートし、発育中の赤ちゃんと絆を深め、母親と喜びや心配事を共有する方法を学ぶ機会として、父親の出産前ケアへの参加に大きな価値を見出した。参加者は一般的に、父親は歓迎されていると感じさせられ、予約の間提供者の父親を含めての対応を望んでいたと感じていた。この研究の結果は、父親の参加は出産前ケア提供者が父親の妊娠への積極的な関与、母親のサポート、および親となる準備を促進する機会を提供することを示唆している。 摘要: 父亲在怀孕期间的支持性参与可以对孕产妇和婴儿产生积极影响。父亲在产前护理中的参与正在增加, 但很少有研究去了解母亲和父亲如何体会父亲参与产前护理, 以及他们对父亲参与的偏好。我们采访了初次怀孕的母亲 (N = 22) 和父亲 (N = 20), 以了解父亲参与产前护理的情况, 对护理机构对待父亲的看法, 以及父亲参与的偏好。访谈采用扎根理论的原则进行编码。父亲参与的范围从参加被认为"重要"的探视 (如超声波检查) 到参加每次预约。父亲参与的经历各不相同, 许多人认为这既是支持母亲的重要行为, 也是承担父亲角色的一部分。大多数参与者认为父亲参与产前护理很有价值, 因为这是父亲学习如何支持健康怀孕、与发育中的婴儿建立联系以及与母亲分享快乐或担忧的机会。参与者普遍认为, 父亲受到了欢迎, 并希望护理机构在预约时就包括父亲。这项研究的结果表明, 父亲参与为产前护理机构提供了机会, 以促进父亲积极参与到怀孕过程, 支持母亲以及为父母角色做准备。 ملخص: الأب والشريك: وجهات نظر الأمهات والآباء بشأن مشاركة الأب في الرعاية ما قبل الولادة يمكن أن تؤثر مشاركة الأب الداعمة أثناء الحمل تأثيرا إيجابيا على نتائج الأمهات والأطفال. وبالرغم من تزايد مشاركة الأب في الرعاية السابقة للولادة، لا يوجد سوى القليل من الأبحاث التي تتناول فهم تجارب الأمهات والآباء لمشاركة الأب في الرعاية السابقة للولادة، وتفضيلاتهم بشأن مشاركة الأب. تم مقابلة الأمهات الحوامل لأول مرة (N = 22) والآباء (N = 20) للتعرف على مشاركة الآباء في الرعاية السابقة للولادة، وتصورات معاملة مقدمي الرعاية للآباء، وتفضيلات مشاركة الأب. وتم ترميز المقابلات باستخدام مبادئ نظرية قائمة على البيانات. وتراوحت مشاركة الأب بين حضور زيارات المتابعة التي تعتبر "مهمة" فقط (مثل جلسة الموجات فوق الصوتية) أوالحضور في كل موعد مع الطبيب. وتباينت تجارب مشاركة الأب، حيث وصفها الكثيرون بأنها عمل هام لدعم الأم وجزء من القيام بدور الأب. ورأى معظم المشاركين قيمة كبيرة لمشاركة الأب في الرعاية السابقة للولادة، كفرصة للآباء لتعلم كيفية دعم الحمل الصحي، وتكوين الارتباط بطفلهم النامي، وتقاسم الفرح أو المخاوف مع الأمهات. ورأى المشاركون عموما أن الآباء يشعرون بأنهم موضع ترحيب ويريدون أن يكون الآباء حاضرين أثناء مواعيد المتابعة. وتشير نتائج هذه الدراسة إلى أن مشاركة الأب تتيح الفرصة لمقدمي الرعاية الطبية قبل الولادة لتعزيز مشاركة الآباء الإيجابية في الحمل، ودعم الأمهات، والإعداد للوالدين.